Efeitos da talidomida no tratamento da endometriose experimental em ratas - SOUZA, Isabela Bastos Jácome de (2023)
Endometriosis is a chronic and debilitating disease associated with pelvic pain. Strategies have been researched for pain control, such as the use of anti-inflammatory substances. In this perspective, thalidomide appears as an option in pain control due to its immunomodulatory property used in the treatment of various clinical conditions. The objective of this work was to evaluate the analgesic and anti-inflammatory effect of thalidomide in the treatment of experimental endometriosis. 36 Wistar rats were used and randomly separated into 06 groups: CONTROL (-), LEUPROLIDE, SHAM and groups T25, T50 and T100 with oral administration of 25, 50 and 100 mg/kg/day of thalidomide respectively. Behavioral tests were performed to evaluate pain, evaluate serum levels of cytokines (INF γ, TNF α, IL-6 and IL-10); measurements of implant volumes before and at the end of the treatment protocol and histopathological study of the implant areas. From a dose of 50mg/kg/day, a reduction in the pain threshold was observed in the behavioral tests applied. In the T50 and T100 groups, low levels of TNF α and IL6 were maintained in addition to a reduction in IL10 expression. Very similar levels of IFN-γ were observed between the treated groups and the SHAM group. The T50, T100 and leuprolide groups obtained the least preservation of the ectopic epithelium, indicating a reduction in endometriotic implantation. In the model studied, thalidomide had an analgesic, anti-inflammatory action and reduced the size of the implants, more significantly with doses starting at 50 mg/kg/day, and can be suggested as an option in the treatment of endometriosis pain.